Bridging digital transformation and local wisdom: towards inclusive and sustainable public service delivery in indigenous communities - Jabbar, Abdul; Astuti, Yayuk; Ahmad, Jamaluddin; Adnan, Andi Astinah; Putra, Aswandi (Frontiers in Sustainability, 2026)
The challenges and opportunities of digital transformation in rural and indigenous areas are different from those in urban areas, as are the contexts themselves. This research analyzes the implementation of digital public service reforms in the indigenous communities of Towani Tolotang, Soraja Kulo Dalam, and To Batu Sandobatu, located in Sidenreng Rappang, Indonesia. To accomplish this, a multi-method approach involving document research, fieldwork, interviews, and participant observations was used. The analysis was guided by the concepts of integration pathways, barriers, enabling factors, and impacts, focusing on empowerment, participation, and sustainability. The findings indicate that integration pathways were culturally mediated. In the case of Towani Tolotang, customary elders legitimized reforms, as in Soraja Kulo Dalam, in which youth reform as digital champions. In To Batu Sandobatu, rituals and partnerships with NGOs grant acceptance. Infrastructural gaps, insufficient digital literacy, and distrust are properties of barriers, while inter-generational mediation, customary authority, and government-civil society collaboration constitute the opportunity. The impacts of these dynamics, however, went beyond efficiency by also enabling broader participation, long-term sustainment, and empowerment of digital initiatives. This finding enriches the literature on digital governance in developing countries by providing evidence of the necessity of hybrid governance models to secure inclusion and legitimacy. From a practical standpoint, this means that policymakers should combine infrastructural investment with trust-building, participation enhancement, and culturally respectful strategies. From a theoretical standpoint, this research adds to the discussion of hybrid governance and sustainable digital transformation by conceptualizing empowerment, participation, and sustainability as interconnected outcomes.